2009
DOI: 10.1016/j.worlddev.2008.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Remittances, Institutions, and Economic Growth

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
233
7
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(277 citation statements)
references
References 11 publications
9
233
7
8
Order By: Relevance
“…The underlying theory we use is motivated by a standard growth model where foreign direct investment (FDI), overseas development assistance (ODA), and migrant remittances are all introduced as components of investment (see Burnside and Dollar (2000), Catrinescu et al (2009)). Each financial flow finances the investment that determines economic growth.…”
Section: Theoretical Model and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying theory we use is motivated by a standard growth model where foreign direct investment (FDI), overseas development assistance (ODA), and migrant remittances are all introduced as components of investment (see Burnside and Dollar (2000), Catrinescu et al (2009)). Each financial flow finances the investment that determines economic growth.…”
Section: Theoretical Model and Literature Reviewmentioning
confidence: 99%
“…Catrinescu et al (2009) seek to address this by using a dynamic panel GMM specification, employing data from the Inter Country Risk Guide (ICRG).…”
Section: Interactions Between Remittances and Institutionsmentioning
confidence: 99%
“…Indeed, the authors found significant negative interaction terms and interpreted these results as indicative of the credit constraint hypothesis; total remittances appeared to have positive effects on growth only in countries with small financial sectors where presumably credit constraints would be more pervasive. Another study, by Catrinescu and others [26], incorporated institutional variables into the analysis, which covered 114 countries during the 1991-2003 period. Catrinescu and colleagues conducted OLS cross-sectional and various static and dynamic panel regressions of per capita GDP growth on the (log of) total remittances-to-GDP, controlling for initial GDP per capita, ratios of gross capital formation and net private capital inflows to GDP, and such institutional variables as the United Nations Human Development Index, six governance indicators as in Kaufmann, Kraay, and Mastruzzi [62], and risk ratings from the International Country Risk Guide (ICRG).…”
Section: Introductionmentioning
confidence: 99%
“…Remittances can also reduce labor market participation rates as receiving households opt to live of migrants' transfers rather than by working. Moreover, remittances' effect on growth and poverty might reduce the incentives for implementing sound macroeconomic policy or to institute necessary structural reforms (Catrinescu, Leon-Ledesma, Piracha and Quillin, 2009). These differences in results stem certainly from differences across countries regarding institutional aspects and various structural features, from different empirical frameworks and from various channels involved in such relationship.…”
Section: Remittances and Economic Growth Recent Empirical Debatementioning
confidence: 99%